ChemInform Abstract: One‐Pot Sequential Reaction for the Synthesis of Polysubstituted 3‐(3‐Nitro‐2‐phenylchroman‐4‐yl)‐3‐arylaminoacrylates. Issue 26 (1st July 2014) - Zhang, Lili; Sun, Jing; Yan, Chaoguo
Abstract The title compounds (IV) (12 examples) are obtained with high diastereoselectivity and without any catalyst.